If Freud Were a Woman: Gender, Uncertainty, and the Psychology of Being Human. Issue 6 (18th August 2017) - Brothers, Doris
ABSTRACT: This article explores the relationships among gender, uncertainty, and the experience of being human by imagining how psychoanalysis might have evolved had Freud been born female. Since the uncertainty heard in many women's voices goes hand in hand with their relational focus, I suggest that Freud, the woman, would have developed a trauma-centered theory with an ethical foundation reflecting our human relational longings.